PENDEKATAN METODE RULE BASED DALAM MENGALIHBAHASAKAN TEKS BAHASA INGGRIS KE TEKS BAHASA INDONESIA - Utami, Ema; Hartati, Sri (Institute of Research and Community Outreach - Petra Christian University, 2007)
Natural Language Processing is computer ability to process language, written and oral which was used by human in daily conversation. For computation process, language must be presented as simbolic line which follows certain rule. This English text translation into Indonesian text uses Rule Based method because it was done bilingually with different grammar. This English text translator to Indonesian is able to translate the sentences in daily conversation sentences that is close to its original meaning, so that it could help The English learning process to be easier. English text translator to Indonesian is able to detect group of sentences within several paragraphs for one input execution. The general pattern of Explaining-Explained which was found in English language could be translated into Explained-Explaining which follows Indonesian general grammar. The use of Rule Based method with parsing tree based and production rule in English text translator to Indonesian is able to handle the different grammar rule from both languages, so that it produces the suitable translation. Abstract in Bahasa Indonesia : Natural Language Processing (Pemrosesan Bahasa Alami) merupakan kemampuan suatu komputer untuk memproses bahasa, baik lisan maupun tulisan yang digunakan oleh manusia dalam komunikasi sehari-hari. Untuk proses komputasi, bahasa harus dipresentasikan sebagai rangkaian simbol yang memenuhi aturan tertentu. Penerjemahan teks bahasa Inggris ke bahasa Indonesia menggunakan metode Rule Based karena penerjemahan dilakukan secara bilingual (dua bahasa) yang mempunyai tata bahasa yang berbeda. Penerjemah teks bahasa Inggris ke teks bahasa Indonesia ini dapat menerjemahkan kalimat-kalimat dalam